Melatonin in the management of perinatal hypoxic-ischemic encephalopathy: light at the end of the tunnel? - Hendaus MA (Dove Medical Press, 2016)
Mohamed A Hendaus,1,2 Fatima A Jomha,3 Ahmed H Alhammadi1,2 1Department of Pediatrics, Section of Academic General Pediatrics, Hamad Medical Corporation, 2Department of Clinical Pediatrics, Weill-Cornell Medical College, Doha, Qatar; 3School of Pharmacy, Lebanese International University, Khiara, Lebanon Abstract: Perinatal hypoxic-ischemic encephalopathy (HIE) affects one to three per 1,000 live full-term births and can lead to severe and permanent neuropsychological sequelae, such as cerebral palsy, epilepsy, mental retardation, and visual motor or visual perceptive dysfunction. Melatonin has begun to be contemplated as a good choice in order to diminish the neurological sequelae from hypoxic-ischemic brain injury. Melatonin emerges as a very interesting medication, because of its capacity to cross all physiological barriers extending to subcellular compartments and its safety and effectiveness. The purpose of this commentary is to detail the evidence on the use of melatonin as a neuroprotection agent. The pharmacologic aspects of the drug as well as its potential neuroprotective characteristics in human and animal studies are described in this study. Melatonin seems to be safe and beneficial in protecting neonatal brains from perinatal HIE. Larger randomized controlled trials in humans are required, to implement a long-awaited feasible treatment in order to avoid the dreaded sequelae of HIE. Keywords: melatonin, hypoxia, use, encephalopathy